Measuring Trends in Health Inequalities across Urban Cities in Canada: A Focus on Health System Outcomes. (2018) - Nichols, Meredith; Chuang, Junior; Grimwood, Sara; Hynes, Geoff; Harvey, Jean; Plante, Charles; Neudorf, Cory; Allin, Sara
No abstract available